When oriental flavors complemented local cuisine:Chifas in Piura and their inclusion in the regional gastronomic culture - Gutiérrez Rivas, Julissa (2023)
The Piura region, in northern Peru, is recognized at the cultural and tourist level as an outstanding space for its intangible heritage, both artistic and gastronomic. The latter has been highlighted through National Declarations of Heritage as the one concerning Picanterías and chicherías piuranas cultural spaces (2015). Nevertheless, the cultural tradition of Piura, in all its forms, as has happened in Peru, has been enriched through the contributions of different migrant groups, such as the Chinese, coexisting and creating a diverse culinary culture, with practices and flavors appropriate and resigned by the local collective memory. Piura was a department that, in the second half of the 19th century, received a minority Chinese migrant population, compared to regions such as Lambayeque and La Libertad (Gutiérrez and Vargas, 2016, p. 76).   But, as happened in other places with higher migration density, the fondas had an early appearance and, later, the chifas. What products did they offer and how was this cuisine received by the local population? What local inputs would they have provided in this easy incorporation of chifa into the tables of Piura's population? And what memories are associated with these gastronomic spaces? And what memories are associated with these gastronomic spaces? are some questions that, from the documentary and testimonial research, we outline in a first approach to this topic not addressed in the historical literature on the Piura region.